Serum Levels of Fatty Acid Binding Protein 5 Decreased in Squamous Cell Lung Carcinoma - Mansouri, Mahsa; Mojtahedi, Zahra; Ghayyoumi, Mohammad Ali; Montazari, Narges; Sahraian, Hamidreza; Ghalamfarsa, Ghasem (Galen Medical Journal, 2023)
Background: The aberrant expression of Dickkopf-1 (DKK1), triose phosphate isomerase (TPI) and fatty acid binding-protein 5 (FABP5) in lung cancer tissues and their presence in secretome of lung cancer cell lines were reported. Here, serum levels of these molecules in lung cancer patients were compared to those in a healthy control group.Materials and Methods: The patients’ group consisted of 50 newly diagnosed male patients with a mean age of 65.3±11.5 years (27 squamous cell carcinoma (SCC), 7 adenocarcinoma, and 16 small cell carcinoma). Thirty eight apparently healthy men (mean aged 65.1±11.4) served as the control group. ELISA was employed for quantification.Results: Comparison between patients and controls revealed no significant difference, although FABP5 level was lower in patients (3.2 vs. 4.8; p=0.09). Analysis of each type of lung cancer with controls indicated that patients with SCC had significantly lower levels of FABP5 than in controls (2.7 vs. 4.8 ng/ml; P=0.03).Conclusion: Comparison between patients and controls revealed no significant difference, although FABP5 level was lower in patients (3.2 vs. 4.8; p=0.09). Analysis of each type of lung cancer with controls indicated that patients with SCC had significantly lower levels of FABP5 than in controls (2.7 vs. 4.8 ng/ml; P=0.03).[GMJ. 2014;3(4):222-7]